The effect of waste office white paper content and size on the mechanical and thermal properties of low-density polyethylene (LDPE) composites - Salmah, Hussain. Prof. Madya Dr. Ir.; Faisal, Amri (Taylor & Francis, 2010)
Link to publisher's homepage at http://www.taylorandfrancisgroup.com/